Aymara Indian perspectives on development in the Andes - Eisenberg, Amy, 1954- (University of Alabama Press, 2013)
Aymara Indians are a geographically isolated Indigenous people living in the Andes Mountains near Chile's Atacama Desert, one of the most arid regions of the world. As rapid economic growth in the area has begun to divert scarce water to hydroelectric and agricultural projects, the Aymara struggle to maintain their sustainable and traditional systems of water use, agriculture, and pastoralism. In this book, the author provides a detailed exploration of the ethnoecological dimensions of the tension between the Aymara, whose economic, spiritual, and social life are inextricably tied to land and water, and three major challenges: the paving of Chile Highway 11, the diversion of the Altiplano waters of the Río Lauca for irrigation and power-generation, and Chilean national park policies regarding Aymara communities, their natural resources, and cultural properties within Parque Nacional Lauca, the International Biosphere Reserve.